Предмет: Алгебра, автор: balakin05

выполните умножение: (x+1) (x+2)=                                                                                                                         (а+b) (a+b)=                                                                                                                         (a-2) (3-a)=                                                                                                                           (a-b) (a-b)=                                                                                                                           (3x+2y) (3x+2y)=

Ответы

Автор ответа: АннаАрт
0
(x+1)(x+2) = x^2+2x+x+2 = x^2+3x+2

(а+b)(a+b) = a^2+ab+ab+b^2 = a^2+2ab+b^2

(a-2)(3-a) = 3a-a^2-6+2a = -a^2+5a-6

(a-b)(a-b) = a^2-ab-ab+b^2 = a^2-2ab+b^2

(3x+2y)(3x+2y) = 9x^2+6xy+6xy+4y^2 = 9x^2+12xy+4y^2
Автор ответа: balakin05
0
что значит ^
Автор ответа: АннаАрт
0
степень
Автор ответа: АннаАрт
0
x*x=x^2 например
Автор ответа: balakin05
0
спс
Похожие вопросы
Предмет: Русский язык, автор: bmasa437